Analysis of Characteristics of Planetary CVT with the Feature of Over zero Adjustable Speed - 郑甲红; 周志明; 王遒信; 刘立庆 (Jixie chuandong)
This paper introduces the evolution from type NN and WW planetary transmissions into planetary continuously variable speed transmission（Planetary CVT）.The main points of the study are the kinematics,efficiency,variation of out speed and the design theory of positive stop of output element in over zero adjustable speed.